Magnesium hydroxide with low oil absorption value, preparation method thereof and halogen-free low-smoke flame-retardant cable material
By wet modification of the composite modifier powder of magnesium hydroxide, the problem of poor dispersion and compatibility in polymer materials is solved, and the processing performance and mechanical properties of halogen-free low-smoke flame-retardant cable materials are improved. , while maintaining the flame retardant effect.
Patent Information
- Application Number
- CN202411368956.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
Magnesium hydroxide is poor in dispersion and compatibility in polymer materials, resulting in "acidiness" on the surface of the material, white spots or loss of luster, and poor flame retardant and carbon-forming properties. High doses are required to meet the flame retardant requirements, affecting the mechanics of the material. Performance and machining performance.
The composite modifier is used to perform wet surface modification of magnesium hydroxide powder, and anionic and nonionic surfactants with HLB >10 are used to reduce the oil absorption value of magnesium hydroxide and improve its phase with polymer materials. Capacity.
It significantly improves the dispersion and compatibility of magnesium hydroxide in polymer materials, improves the processing performance and mechanical properties of halogen-free low-smoke flame-retardant cable materials, while maintaining the flame retardant effect.
Smart Images

Figure BDA0005067042070000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, and in particular to magnesium hydroxide with low oil absorption value, a preparation method thereof and a halogen-free and low-smoke flame retardant cable material. Background Art
[0002] Magnesium hydroxide is a green, environmentally friendly, high-efficiency smoke-suppressing flame retardant. It produces water by decomposition and vaporization, absorbs heat, dilutes the surrounding oxygen concentration, and thus has a flame retardant effect. However, magnesium hydroxide has a high surface energy and has the properties of "hydrophilic and oleophobic". It has poor dispersibility and compatibility when directly added to polymer materials, which affects the processing properties of composite materials and causes the surface of the material to "acidify", develop white spots or lose its luster. Second, magnesium hydroxide has poor flame retardant charring properties and low flame retardant efficiency. It needs to be added in relatively large amounts. Especially in polymer wires and cables, the mass fraction of magnesium hydroxide is required to reach more than 60% to meet the flame retardant requirements, which directly leads to a decrease in the mechanical properties and processing properties of the material. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide magnesium hydroxide with low oil absorption value and a preparation method thereof and a halogen-free, low-smoke, flame-retardant cable material.
[0004] The present invention solves the technical problem by adopting the following technical solutions.
[0005] The invention provides a method for preparing magnesium hydroxide with low oil absorption value, which comprises: surface modification of magnesium hydroxide powder by using a composite modifier, wherein the composite modifier comprises an anionic surfactant with HLB>10 and a nonionic surfactant with HLB>10.
[0006] The present invention also provides a magnesium hydroxide with low oil absorption value prepared by the above-mentioned preparation method, and the oil absorption value of the magnesium hydroxide with low oil absorption value is ≤30mL / 100g.
[0007] The present invention also provides a halogen-free low-smoke flame-retardant cable material. The raw materials for preparing the halogen-free low-smoke flame-retardant cable material include the low-oil absorption magnesium hydroxide prepared by the above-mentioned preparation method or the above-mentioned low-oil absorption magnesium hydroxide.
[0008] The present invention has the following beneficial effects:
[0009] The present invention provides a magnesium hydroxide with low oil absorption value and a preparation method thereof and a halogen-free low-smoke flame-retardant cable material. The present invention adopts a wet modification method to successfully attach a composite modifier to the surface of magnesium hydroxide, greatly reducing the oil absorption value of magnesium hydroxide without affecting the flame retardant effect of magnesium hydroxide. The magnesium hydroxide with low oil absorption value prepared by the present invention is used in a halogen-free low-smoke flame-retardant cable material, which can significantly improve the dispersibility and compatibility of the magnesium hydroxide with low oil absorption value in polymer materials, and effectively improve the processing performance and mechanical properties of the halogen-free low-smoke flame-retardant cable material. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0011] The following is a detailed description of a magnesium hydroxide with low oil absorption value and a preparation method thereof and a halogen-free, low-smoke, flame-retardant cable material provided in an embodiment of the present invention.
[0012] In a first aspect, an embodiment of the present invention provides a method for preparing magnesium hydroxide with low oil absorption, comprising: surface modifying magnesium hydroxide powder using a composite modifier, wherein the composite modifier comprises an anionic surfactant with an HLB value >10 and a nonionic surfactant with an HLB value >10.
[0013] The methods for surface modification of magnesium hydroxide mainly include wet modification and dry modification. Compared with dry modification, wet modification has better effect. The present invention uses a wet modification method to modify the surface of magnesium hydroxide powder using a composite modifier, successfully attaches the composite modifier to the surface of magnesium hydroxide, can reduce the oil absorption value of magnesium hydroxide, and maintain the flame retardant properties of magnesium hydroxide. The low oil absorption value magnesium hydroxide of the present invention is used in halogen-free low-smoke flame-retardant cable materials, which can not only increase the filling amount of low oil absorption value magnesium hydroxide per unit volume, but also significantly improve the dispersibility and compatibility of magnesium hydroxide in polymer materials, improve the processing performance and mechanical properties of halogen-free low-smoke flame-retardant cable materials, and thus improve the flame retardant effect.
[0014] In some optional embodiments, the anionic surfactant with HLB>10 includes one or more of sodium stearate, sodium oleate, sodium rosin acid, and sodium dodecylbenzene sulfonate; the non-ionic surfactant with HLB>10 includes one or more of Tween 20, Tween 40, Tween 60, and Tween 80.
[0015] The composite modifier of the above composition can play an additive and synergistic role, reduce the surface tension of the solution, successfully attach the composite modifier to the surface of magnesium hydroxide, thereby reducing the oil absorption value of magnesium hydroxide, and the composite modifier is an organic modifier, which improves the flame retardant carbonization of magnesium hydroxide. It can be seen that the surface of magnesium hydroxide powder is modified by the method provided by the embodiment of the present invention, which can reduce the oil absorption value of magnesium hydroxide and improve the compatibility with polymer materials. At the same time, it is used as a carbon source for flame retardants to improve carbonization performance and improve the flame retardant effect of magnesium hydroxide flame retardant, effectively solving the problem that magnesium hydroxide is not easy to disperse in materials and has poor flame retardant effect.
[0016] In some optional embodiments, the mass ratio of anionic surfactants with HLB>10 to nonionic surfactants with HLB>10 is 2:1 to 8:1. Among them, the nonionic surfactants with HLB>10 mainly play the role of dispersing magnesium hydroxide, and the anionic surfactants with HLB>10 perform surface modification on magnesium hydroxide powder. The two can promote each other, making the modification effect better than a single modifier.
[0017] In some optional embodiments, the amount of the composite modifier is 1 to 10% of the total mass of the magnesium hydroxide powder.
[0018] In some optional embodiments, the process comprises the following steps: dripping a composite modifier into a magnesium hydroxide slurry under stirring and heating conditions, and filtering, washing and drying after the reaction is completed to obtain magnesium hydroxide with low oil absorption value.
[0019] The method for preparing magnesium hydroxide with low oil absorption value provided by an embodiment of the present invention comprises the following steps: under stirring and heating conditions, a composite modifier is dripped into a magnesium hydroxide slurry; during the modification process, a nonionic surfactant with an HLB value of more than 10 is coated on the surface of the magnesium hydroxide powder by virtue of the effect of intermolecular polarity, so that the magnesium hydroxide forms a better suspension in water, thereby preventing a large amount of magnesium hydroxide from sinking to the bottom and improving the modification efficiency; and an anionic surfactant with an HLB value of more than 10 is coated on the surface of the magnesium hydroxide by virtue of the effect of intermolecular polarity. 2+ A chemical reaction occurs to form higher fatty acid salts, which are adsorbed on the surface of magnesium hydroxide and enhance the compatibility with polymer materials.
[0020] In some optional implementations, the magnesium hydroxide slurry is obtained by fully mixing magnesium hydroxide powder and deionized water, and the mass fraction of the magnesium hydroxide slurry is 5-10%.
[0021] In some optional embodiments, the reaction temperature is 60-80° C., and the reaction time is 60-120 minutes.
[0022] In some optional embodiments, the drying temperature is 110° C. and the drying time is 24 hours.
[0023] In a second aspect, an embodiment of the present invention further provides a magnesium hydroxide with low oil absorption value prepared by the above-mentioned preparation method, wherein the oil absorption value of the magnesium hydroxide with low oil absorption value is ≤30 mL / 100 g.
[0024] In a third aspect, an embodiment of the present invention further provides a halogen-free, low-smoke, flame-retardant cable material, wherein the raw materials for preparing the halogen-free, low-smoke, flame-retardant cable material include the low-oil-absorption magnesium hydroxide prepared by the above-mentioned preparation method or the above-mentioned low-oil-absorption magnesium hydroxide.
[0025] In some optional embodiments, the following components are included in weight proportions: 10 to 30 parts of ethylene-vinyl acetate copolymer, 10 to 30 parts of linear low-density polyethylene, 40-60 parts of magnesium hydroxide with low oil absorption value, and 5 to 10 parts of functional additives, wherein the functional additives include one or more of a compatibilizer, a stabilizer, a lubricant and an antioxidant.
[0026] The present invention will be further described below in conjunction with the embodiments.
[0027] The magnesium hydroxide used in the following examples and comparative examples is produced by Weifang Wanfeng New Material Technology Co., Ltd., and the model is MH-01. The functional materials used in the preparation process of the halogen-free low-smoke flame-retardant cable material are the same.
[0028] Example 1
[0029] Preparation of magnesium hydroxide with low oil absorption value: Weigh 50g of magnesium hydroxide, add deionized water to prepare a slurry with a mass fraction of 5%, heat to 80°C, and stir at a speed of 800r / min. Weigh 1.6g of sodium stearate and 0.4g of Tween 20, dilute with anhydrous ethanol, and slowly add to the slurry. After the addition is completed, continue stirring for 90 minutes, filter to obtain a white solid, wash it with deionized water several times, and dry it at 110°C for 24 hours to obtain magnesium hydroxide with low oil absorption value.
[0030] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 20 parts of ethylene-vinyl acetate copolymer, 20 parts of linear low-density polyethylene, 50 parts of low oil absorption magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and get a halogen-free, low-smoke, flame-retardant cable material sample.
[0031] Example 2
[0032] Preparation of magnesium hydroxide with low oil absorption value: Weigh 50g of magnesium hydroxide, add deionized water to prepare a slurry with a mass fraction of 8%, heat to 80°C, and stir at a speed of 800r / min. Weigh 0.8g of sodium oleate and 0.2g of Tween 20, dilute with anhydrous ethanol, and slowly add them to the slurry. After the addition is completed, continue stirring for 90 minutes, filter to obtain a white solid, wash it with deionized water several times, and dry it at 110°C for 24 hours to obtain magnesium hydroxide with low oil absorption value.
[0033] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 10 parts of ethylene-vinyl acetate copolymer, 30 parts of linear low-density polyethylene, 50 parts of low oil absorption magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and get a halogen-free, low-smoke, flame-retardant cable material sample.
[0034] Example 3
[0035] Preparation of magnesium hydroxide with low oil absorption value: Weigh 50g of magnesium hydroxide, add deionized water to prepare a slurry with a mass fraction of 8%, heat to 80°C, and stir at a speed of 800r / min. Weigh 2g of sodium rosin acid and 1g of Tween 20, dilute with anhydrous ethanol, and slowly add to the slurry. After the addition is completed, continue stirring for 60 minutes, filter to obtain a white solid, wash it with deionized water several times, and dry it at 110°C for 24 hours to obtain magnesium hydroxide with low oil absorption value.
[0036] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 15 parts of ethylene-vinyl acetate copolymer, 20 parts of linear low-density polyethylene, 60 parts of low-oil-absorption magnesium hydroxide, and 5 parts of functional additives. Put them into a mixer, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and get a halogen-free, low-smoke, flame-retardant cable material sample.
[0037] Example 4
[0038] Preparation of magnesium hydroxide with low oil absorption value: Weigh 50g of magnesium hydroxide, add deionized water to prepare a slurry with a mass fraction of 10%, heat to 80°C, and stir at a speed of 800r / min. Weigh 1.6g of sodium dodecylbenzene sulfonate and 0.4g of Tween 20, dilute with anhydrous ethanol, and slowly add to the slurry. After the addition is completed, continue stirring for 90 minutes, filter to obtain a white solid, wash it with deionized water several times, and dry it at 110°C for 24 hours to obtain magnesium hydroxide with low oil absorption value.
[0039] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 25 parts of ethylene-vinyl acetate copolymer, 25 parts of linear low-density polyethylene, 40 parts of low oil absorption magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and get a halogen-free, low-smoke, flame-retardant cable material sample.
[0040] Example 5
[0041] Preparation of magnesium hydroxide with low oil absorption value: Weigh 50g of magnesium hydroxide, add deionized water to prepare a slurry with a mass fraction of 8%, heat to 60°C, and stir at a speed of 800r / min. Weigh 4g of sodium stearate and 1g of Tween 20, dilute with anhydrous ethanol, and slowly add them dropwise to the slurry. After the addition is completed, continue stirring for 90 minutes, filter to obtain a white solid, wash it with deionized water several times, and dry it at 110°C for 24 hours to obtain magnesium hydroxide with low oil absorption value.
[0042] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 20 parts of ethylene-vinyl acetate copolymer, 20 parts of linear low-density polyethylene, 50 parts of low oil absorption magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and get a halogen-free, low-smoke, flame-retardant cable material sample.
[0043] Example 6
[0044] Preparation of magnesium hydroxide with low oil absorption value: Weigh 50g of magnesium hydroxide, add deionized water to prepare a slurry with a mass fraction of 8%, heat to 80°C, and stir at a speed of 800r / min. Weigh 4g of sodium stearate and 0.5g of Tween 20, dilute with anhydrous ethanol, and slowly add to the slurry. After the addition is completed, continue stirring for 120 minutes, filter to obtain a white solid, wash it with deionized water several times, and dry it at 110°C for 24 hours to obtain magnesium hydroxide with low oil absorption value.
[0045] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 30 parts of ethylene-vinyl acetate copolymer, 10 parts of linear low-density polyethylene, 50 parts of low oil absorption magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and get a halogen-free, low-smoke, flame-retardant cable material sample.
[0046] Comparative Example 1
[0047] The ordinary magnesium hydroxide on the market is produced by Weifang Wanfeng New Material Technology Co., Ltd., model MH-01, and has not undergone any modification.
[0048] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 20 parts of ethylene-vinyl acetate copolymer, 20 parts of linear low-density polyethylene, 50 parts of magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and obtain a halogen-free, low-smoke, flame-retardant cable material sample.
[0049] Comparative Example 2
[0050] The steps are similar to those in Example 1, except that the amount of sodium stearate is 1.8 g and the amount of Tween 20 is 0.2 g.
[0051] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 20 parts of ethylene-vinyl acetate copolymer, 20 parts of linear low-density polyethylene, 50 parts of magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and obtain a halogen-free, low-smoke, flame-retardant cable material sample.
[0052] Comparative Example 3
[0053] The steps are similar to those of Example 1, except that the amount of sodium stearate is 0.32 g and the amount of Tween 20 is 0.08 g.
[0054] Preparation of halogen-free, low-smoke, flame-retardant cable material: prepare 20 parts of ethylene-vinyl acetate copolymer, 20 parts of linear low-density polyethylene, 50 parts of magnesium hydroxide, and 10 parts of functional additives. Put them into a mixer respectively, add plastic particles first, then add powder materials, and mix for 8 minutes. Take out the mixture, put it into a tablet press to form, and obtain a halogen-free, low-smoke, flame-retardant cable material sample.
[0055] The magnesium hydroxide powders obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were tested for oil absorption, and the mechanical properties and flame retardant properties of the halogen-free low-smoke cable material samples were tested. The test results are shown in Table 1.
[0056] The test method for oil absorption value is carried out in accordance with GB / T5211.15-2014 standard, the test method for mechanical properties is carried out in accordance with GB / T1040.3-2006 standard, and the test method for flame retardant properties is carried out in accordance with GB / T2406.2-2009 standard.
[0057] The test results of oil absorption value, mechanical properties and flame retardant properties of the products obtained in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1 below.
[0058] Table 1
[0059]
[0060] From the comparison of Examples 1 to 6 and Comparative Examples 1 to 3 in Table 1 above, it can be seen that the oil absorption values of the magnesium hydroxide powders treated with the composite modifier in Examples 1 to 6 are all reduced, and the amount of the composite modifier, the modification time, and the modification temperature can all affect the oil absorption value of magnesium hydroxide, generally showing a positive correlation trend, and the modification effect of sodium stearate / Tween 20 is the best. The tensile strength and elongation at break of the halogen-free, low-smoke, flame-retardant cable material prepared using low-oil-absorption magnesium hydroxide are greatly improved, while the oxygen index is basically unchanged, indicating that the dispersibility and compatibility of low-oil-absorption magnesium hydroxide in the cable matrix material become better, effectively improving the processing performance and mechanical properties of the halogen-free, low-smoke, flame-retardant cable material.
[0061] By analyzing the results of the embodiments of the present invention and the comparative examples, it can be seen that: (1) the oil absorption value of the magnesium hydroxide powder treated with the composite modifier in the embodiments is reduced; (2) the tensile strength and elongation at break of the halogen-free, low-smoke, flame-retardant cable material prepared using low oil absorption magnesium hydroxide are greatly improved, while the oxygen index is basically unchanged; (3) the oil absorption value of the low oil absorption magnesium hydroxide obtained by the preferred experimental parameters is ≤30mL / 100g.
[0062] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing magnesium hydroxide with low oil absorption value, characterized in that: The method comprises: performing surface modification on magnesium hydroxide powder by using a composite modifier, wherein the composite modifier comprises an anionic surfactant with an HLB value greater than 10 and a nonionic surfactant with an HLB value greater than 10.
2. The preparation method according to claim 1, characterized in that: The anionic surfactant with HLB>10 includes one or more of sodium stearate, sodium oleate, sodium rosin acid, and sodium dodecylbenzene sulfonate; the nonionic surfactant with HLB>10 includes one or more of Tween 20, Tween 40, Tween 60, and Tween 80.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the anionic surfactant with an HLB value greater than 10 to the nonionic surfactant with an HLB value greater than 10 is 2:1 to 8:
1.
4. The preparation method according to claim 1, characterized in that: The amount of the composite modifier is 1-10% of the total mass of the magnesium hydroxide powder.
5. The preparation method according to claim 1, characterized in that: The following steps are involved: Under stirring and heating conditions, a composite modifier is added dropwise to the magnesium hydroxide slurry. After the reaction is completed, the slurry is filtered, washed and dried to obtain magnesium hydroxide with low oil absorption value.
6. The preparation method according to claim 5, characterized in that: The magnesium hydroxide slurry is obtained by fully mixing magnesium hydroxide powder and deionized water, and the mass fraction of the magnesium hydroxide slurry is 5-10%.
7. The preparation method according to claim 5, characterized in that: The reaction temperature is 60-80° C., the reaction time is 60-120 minutes, the drying temperature is 110° C., and the drying time is 24 hours.
8. A magnesium hydroxide with low oil absorption value prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The oil absorption value of the low oil absorption value magnesium hydroxide is ≤30mL / 100g.
9. A halogen-free low-smoke flame-retardant cable material, characterized in that: The raw material for preparing the halogen-free low-smoke flame-retardant cable material includes the low-oil absorption magnesium hydroxide prepared by the preparation method described in any one of claims 1 to 7 or the low-oil absorption magnesium hydroxide described in claim 8.
10. The halogen-free low-smoke flame-retardant cable material according to claim 9, characterized in that: The invention comprises the following components in parts by weight: 10 to 30 parts of ethylene-vinyl acetate copolymer, 10 to 30 parts of linear low-density polyethylene, 40 to 60 parts of magnesium hydroxide with low oil absorption value, and 5 to 10 parts of functional additives, wherein the functional additives comprise one or more of a compatibilizer, a stabilizer, a lubricant and an antioxidant.
